Customer satisfaction on MangkukTingkat.com service delivery / Fatanah Ibrahim - Ibrahim, Fatanah (2013)
This study surveyed on the customer satisfaction toward MangkukTingkat.com service delivery. The researcher analyzed 291 samples from MangkukTingkat.com’s customer in order to examine the influence of service delivery towards customer satisfaction, customer satisfaction on the behavioural intention and the mediating effect of customer satisfaction between service delivery and behavioural intention. The questionnaire has been distributed via email since the services offered by MangkukTingkat.com are online basis. Based from the findings, it showed there is significant relationship between service delivery and customer behavioural intention. On the other hand, customer satisfaction is positively related to customer behavioural intention. Therefore, this study is beneficial to the company whereby they can improve their services by understanding customer’s requirements for them to projected higher return. Although, there are some limitation in this study which has been identified and being discussed, in future research they may look into more perspectives which can contributes to the body of knowledge in hospitality industry.